2014
DOI: 10.2196/jmir.3651
|View full text |Cite
|
Sign up to set email alerts
|

Use of Home Telemonitoring to Support Multidisciplinary Care of Heart Failure Patients in Finland: Randomized Controlled Trial

Abstract: BackgroundHeart failure (HF) patients suffer from frequent and repeated hospitalizations, causing a substantial economic burden on society. Hospitalizations can be reduced considerably by better compliance with self-care. Home telemonitoring has the potential to boost patients’ compliance with self-care, although the results are still contradictory.ObjectiveA randomized controlled trial was conducted in order to study whether the multidisciplinary care of heart failure patients promoted with telemonitoring lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
2
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(187 citation statements)
references
References 32 publications
(39 reference statements)
4
162
2
7
Order By: Relevance
“…In our study one patient with extreme illness anxiety became very fearful and withdrew almost immediately after installation. Other RCTs involving telemonitoring have listed anxiety as a reason for withdrawal [34]. This may be reduced by the presence of an informal caregiver in the home [35], a finding which we also identified.…”
Section: Discussionsupporting
confidence: 59%
“…In our study one patient with extreme illness anxiety became very fearful and withdrew almost immediately after installation. Other RCTs involving telemonitoring have listed anxiety as a reason for withdrawal [34]. This may be reduced by the presence of an informal caregiver in the home [35], a finding which we also identified.…”
Section: Discussionsupporting
confidence: 59%
“…Overall, 22 of the 28 studies (79%) demonstrated that using mobile phone features (text messaging, mobile apps, telemonitoring via mobile phones) was effective in improving behavioral and clinical outcomes. This review includes studies targeting a variety of CV conditions: CHD (12), 1829 chronic HF (6), 3035 HTN (5), 3640 stroke (2), 4142 acute coronary syndrome (1), 43 CVD (1), 44 and metabolic syndrome (1). 45 A dominant number of studies examined medication adherence as the clinical outcome (10 studies) while other studies examined outcomes such as PA, cardiac rehabilitation (CR) adherence, or a combination of CVD risk factors (blood pressure/BP, cholesterol, body mass index, weight).…”
Section: Resultsmentioning
confidence: 99%
“…24,26,29,[44][45][46]50,51 Due to the cost of technology, this method of delivery of care highlights a digital divide, and it creates a sense of exclusivity and complexity which can create limitations based on the user's abilities. [23][24][25][30][31][32][33]37,39,43,45,46,55 This theme encompassed observations that organisations need additional technical personnel to handle the additional workload associated with this new modality of care.…”
Section: Barriersmentioning
confidence: 99%